2003
DOI: 10.1074/jbc.m308297200
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Diversity among the 1-Amino-cyclopropane-1-Carboxylate Synthase Isozymes Encoded by the Arabidopsis Gene Family

Abstract: 1-Amino-cyclopropane-1-carboxylate synthase (ACS, EC 4.4.1.14) is the key enzyme in the ethylene biosynthetic pathway in plants. The completion of the Arabidopsis genome sequence revealed the presence of twelve putative ACS genes, ACS1-12, dispersed among five chromosomes. ACS1-5 have been previously characterized. However, ACS1 is enzymatically inactive whereas ACS3 is a pseudogene. Complementation analysis with the Escherichia coli aminotransferase mutant DL39 shows that ACS10 and 12 encode aminotransferases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
302
0
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 312 publications
(322 citation statements)
references
References 69 publications
14
302
0
6
Order By: Relevance
“…Auxin induces ethylene biosynthesis in many plants (Yang and Hoffman, 1984); indeed, most of the Arabidopsis ACS (ACC synthase) genes are induced following auxin treatment (Yamagami et al, 2003;Tsuchisaka and Theologis, 2004). Although the auxin-induced inhibition of pea root elongation appears not be mediated by ethylene (Eliasson et al, 1989), we observed that silver ion supplementation dramatically muted the inhibition of wild-type Arabidopsis root elongation by IAA.…”
Section: Cullin Modification Is Defective In Ecr1-1mentioning
confidence: 59%
“…Auxin induces ethylene biosynthesis in many plants (Yang and Hoffman, 1984); indeed, most of the Arabidopsis ACS (ACC synthase) genes are induced following auxin treatment (Yamagami et al, 2003;Tsuchisaka and Theologis, 2004). Although the auxin-induced inhibition of pea root elongation appears not be mediated by ethylene (Eliasson et al, 1989), we observed that silver ion supplementation dramatically muted the inhibition of wild-type Arabidopsis root elongation by IAA.…”
Section: Cullin Modification Is Defective In Ecr1-1mentioning
confidence: 59%
“…Various reports have shown that plant ACC synthase can serve the same function in E. coli (Van Der Straeten et al 1990;Tarun et al 1998;Yamagami et al 2003). Tarun et al (1998) integrated the ACC deaminase gene into the genome of the mutant strain JHM544, which is an Ile auxotroph, and developed the E. coli strain JAde 6, which is effective for testing putative ACC synthases.…”
Section: Resultsmentioning
confidence: 99%
“…The cDNA of AtACS7 was isolated using the method described by Yamagami et al (2003). As a positive control in the cucumber plants, CsACS1G (Knopf and Trebitsh 2006), encoded by the well-characterized F gene, was also used to test its biochemical activity.…”
Section: Prokaryotic Expression Systemmentioning
confidence: 99%
“…ACS5 has been shown to be an enzymatically active ACS (Yamagami et al, 2003), the product of which is ACC, the immediate precursor for ethylene. Ethylene has been shown to play a role in regulating anisotropic growth.…”
Section: Role Of Acs5 In the Sos5/fei Pathwaymentioning
confidence: 99%